Zmiana treści stosunku pracy mianowanego urzędnika służby cywilnej - Wróbel, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article presents the issue of the changes to the employment of the appointed civil servant on the ground of Polish labor law. The main assumption is to designate differences between changes to the employment of contractual employees and changes to the employment of appointed civil servants. This division originates from the conception of civil service which is strongly connected with the administrative law. The author also points to the requirements which have to be met in case of employment changes and emphasizes the importance and significance of unilateral orders which designate assumptions of the employment relationships entered on the grounds of appointment. The main objective of the paper is to draw attention to the statutory requirements specifi ed in the Civil Service Act. Furthermore, at the same time, the article points to the practical aspects of appointed employment relationship modifications.
Keywords: urzędnik służby cywilnej; ustanowiony stosunek pracy; jednostronne zlecenia; dyspozycyjność; podporządkowanie; zmiany stosunku pracy